2019
DOI: 10.25105/imar.v16i2.4678
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Knowledge and Understanding Taxation, Quality of Tax Services, and Tax Awareness on Personal Tax Compliance

Abstract: <p>The purpose of this study is to find out a significant influence between Knowledge and Understanding of Taxation, Tax Service Quality, and Tax Awareness on the Compliance of Individual Taxpayers registered at the KPP of Jakarta Penjaringan. The research method used is multiple regression analysis. The data used are primary data; a sample is determined by convenience sampling method, data collected using a questionnaire. Respondents in this study amounted to 100 people. The results of this study are kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
2
5
0
3
Order By: Relevance
“…With the tax awareness as one of the important things in the country's development program, people will understand that what they give will be recovered later on. This is supported by the studies carried out by Alfina & Diana (2021), Oktaviani et al (2019), and Subarkah & Dewi (2017), which explain that the awareness of a taxpayer has a positive effect on taxpayer compliance. Consequently, the fourth hypothesis is formulated as follows.…”
Section: Tax Awareness and Taxpayer's Compliancesupporting
confidence: 52%
“…With the tax awareness as one of the important things in the country's development program, people will understand that what they give will be recovered later on. This is supported by the studies carried out by Alfina & Diana (2021), Oktaviani et al (2019), and Subarkah & Dewi (2017), which explain that the awareness of a taxpayer has a positive effect on taxpayer compliance. Consequently, the fourth hypothesis is formulated as follows.…”
Section: Tax Awareness and Taxpayer's Compliancesupporting
confidence: 52%
“…(Newman & Nokhu, 2018) research on SMEs in Zimbabwe shows that SMEs have basic knowledge of taxation but lack understanding of taxes, therefore it is necessary to evaluate taxes and handle corruption in increasing tax taxes. Research (Oktaviani et al, 2019) explains knowledge and understanding, service quality, tax awareness that affects individual taxpayers. Research conducted by (Manual & Xin, 2016; found that an increase in tax knowledge level lead to tax rate increment.…”
Section: The Dynamics Of Tax Knowledgementioning
confidence: 99%
“…In line with research (Newman & Nokhu, 2018) taxpayers have basic knowledge of taxation, but their understanding of taxes is still low. Research (Oktaviani et al, 2019) knowledge and understanding, service quality, tax awareness shows the existence of taxpayers. This explains that tax knowledge was an important factor for tax compliance readiness.…”
Section: Rho_amentioning
confidence: 99%
“…Awareness of paying taxes is the willingness of taxpayers to know, understand and implement tax provisions correctly and voluntarily. The instrument for measuring awareness of paying taxes was developed from Oktaviani (2017) with indicators such as willingness to comply with tax regulations, willingness to serve the state, willingness to participate in state development, willingness to pay taxes, and willingness to advance people's welfare. Measure variables using a Likert scale ranging from 1 (very unconscious) to 5 (very aware) to state the level of awareness of paying taxes.…”
Section: Variable Operational Definitionmentioning
confidence: 99%
“…The results of previous studies on the determinants of tax compliance using the theory of planned behavior are still inconsistent, namely what has been done by Oktaviani (2017), Lesmana et al (2017), , and Damayanti et al (2015). However, replacing one of the variables in the theory of planned behavior, namely the perceived behavioral control variable (Kraft et al, 2005), can develop the theory of planned behavior.…”
Section: Introductionmentioning
confidence: 99%